2017
DOI: 10.1038/s41598-017-04524-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide mapping of DNase I hypersensitive sites reveals chromatin accessibility changes in Arabidopsis euchromatin and heterochromatin regions under extended darkness

Abstract: Light, as the energy source in photosynthesis, is essential for plant growth and development. Extended darkness causes dramatic gene expression changes. In this study, we applied DNase-seq (DNase I hypersensitive site sequencing) to study changes of chromatin accessibility in euchromatic and heterochromatic regions under extended darkness in Arabidopsis. We generated 27 Gb DNase-seq and 67.6 Gb RNA-seq data to investigate chromatin accessibility changes and global gene expression under extended darkness and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 53 publications
8
17
0
Order By: Relevance
“…Consistent with previous work 33 with them repressing gene expression in mesophyll cells 12,13 . In the current dataset, we found that transcription factor binding events predicted to be positive activators were 1.6 and 2.9 times more likely to be found in promoters and introns respectively compared to predicted negative regulators.…”
Section: Chromatin Dynamics and Transcription Factor Binding During Dsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous work 33 with them repressing gene expression in mesophyll cells 12,13 . In the current dataset, we found that transcription factor binding events predicted to be positive activators were 1.6 and 2.9 times more likely to be found in promoters and introns respectively compared to predicted negative regulators.…”
Section: Chromatin Dynamics and Transcription Factor Binding During Dsupporting
confidence: 92%
“…3b). This is consistent with the notion that exposure to light leads to a rapid increase in open chromatin around gene bodies 33 . To further investigate the extent to which accessible chromatin changed over the entire time-course, the proportion of DHS that were shared between time-points was examined (Fig.…”
Section: Chromatin Dynamics Associated With De-etiolation In G Gynandrasupporting
confidence: 92%
See 1 more Smart Citation
“…The public data sets were downloaded from NCBI Gene Expression Omnibus ( http://www.ncbi.nlm.nih.gov/geo/ ) ( 38 ) and Sequence Read Archive ( http://www.ncbi.nlm.nih.gov/sra ) ( 39 ). The in-house data sets of Arabidopsis and rice were previously published ( 34 37 ).…”
Section: Methodsmentioning
confidence: 99%
“…ChIP-seq data for various histone modifications, histone variants and TFs have accumulated in public databases for studies on the regulation of gene expression in developmental processes and in response to environmental treatments in Arabidopsis, rice and maize ( 24 33 ). In addition, our group also accumulated in-house epigenomic data sets, such as DNase-seq and ChIP-seq data for histone modifications and variants in Arabidopsis and rice ( 34 37 ). The abundance of epigenomic data sets enabled construction of a plant chromatin state database to better decode chromatin states with epigenomic data sets and to discover causal functions hidden in plant chromatin.…”
Section: Introductionmentioning
confidence: 99%